FIKIH TASAMUH PENGGUNAAN PENGERAS SUARA PADA SAAT ADZAN - Mujiburrahman, Mujiburrahman; Muhammad Suhufi (Bajang Institute, 2024)
This article contains about the use of loudspeakers during the adhan which has long been done by the Muslim community. As Muslims, the use of loudspeakers has been regulated by Islamic Sharia and positive Law. So the author needs to describe and analyze more deeply related to the use of this loudspeaker. This study aims to provide our comprehensive understanding regarding the use of loudspeakers. This study used a descriptive cutative method. Research data